Avaliação do impacto de psicotrópicos no crescimento e viabilidade celular em culturas de células cancerígenas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
Recent studies have explored the repurposing of fluoxetine, a well-known selective serotonin reuptake inhibitor (SSRI), for its potential anticancer properties. This investigation aimed to evaluate the effects of fluoxetine at dosages ranging from 0.0025 to 0.025 mg/mL on the growth of melanoma (B16F10) and breast adenocarcinoma (4T1) cell cultures. Cultures of B16F10 melanoma cells and 4T1 breast adenocarcinoma cells were treated with fluoxetine at various concentrations (0.0025, 0.005, 0.01, and 0.025 mg/mL). The cell viability was assessed using standard assays, including MTT and trypan blue exclusion, over a 72-hour period. The findings indicated that fluoxetine exhibited a dose-dependent inhibitory effect on cell growth in both B16F10 and 4T1 cell lines. At the highest concentration tested (0.025 mg/mL), a slight but statistically significant reduction in cell viability was observed in comparison to untreated controls. Specifically, B16F10 melanoma cells showed a reduction in viability by approximately 10%, while 4T1 breast adenocarcinoma cells demonstrated a reduction of about 12%. Lower concentrations of fluoxetine (0.0025 mg/mL) resulted in minimal impact on cell growth, suggesting a threshold effect. Fluoxetine, at the tested concentrations, displayed a modest inhibitory effect on the proliferation of melanoma and breast adenocarcinoma cells in vitro. These preliminary results support the potential of fluoxetine as an adjuvant in cancer therapy.
Keywords: Fluoxetina; Melanoma; Adenocarcinoma Mamário; Cultura de Células; Terapia contra o câncer; Viabilidade celular; Farmácia